A Historical Study of Immigration Phenomenon in Undeveloped Societies: Study of Economic Reasons of Immigration during Pahlavi I Period in Zahedan - Yousefifar, Shahram; Riahi, Azam (Journal of History Culture and Art Research, 2017)
During the reign of Reza Shah, policy of magisterial modernization was done on the basis of society modernization by importing products, civilization manifestations, modern management, monopolizing political power and governmentalizing economy. Social structures, under the influence of integration in global system and the effects caused by two world wars, as a semi-periphery region, did not stay away from unpleasant consequences of the situation such as immigration inside the borders of Iran and immigration among the political borders of Iran especially in eastern borders. Because of special geographical situation (border region) and economic situation (silk trade route), eastern borders had an important role in Iran’s exterritorial immigration system and were receptive to resident ethnics in neighbor countries (Hazara in Afghanistan, Sikh, etc.) and were also the entry gate of immigrants to eastern cities of Iran. In this research, emphasizing on Iran’s situation in global system, immigration and its causes on Zahedan have been studied. The results suggest that the strategic location of Zahedan was a predisposing factor of preliminary foundations such as railway for economy growth of the city and a small group of Hindus’ immigration for employment in this part. Gradually, central government actions in customs section and transportation development, turned Zahedan into a suitable region for trade that resulted immigration and habitation of many citizens of neighboring countries in order to work in economic fields. Because of disability in adaption to new conditions and lack of proficiency, many native inhabitants immigrated to the other regions.